The Influence of Progressive Relaxation on Anxiety in Pregnant Women with Hypertension - Rosyadah, Ning Arum Nur; Kundarti, Finta Isti; Rahmaningtyas, Indah; Rahayu, Dwi Estuning (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Hypertensive disorders during pregnancy are a serious issue affecting between 5 percent to 10 percent of all pregnancies globally. Women experiencing hypertension during pregnancy may suffer significant psychological impacts, including anxiety. Progressive muscle relaxation exercises can help reduce muscle tension, enhance feelings of happiness, and alleviate stress and anxiety during pregnancy. The purpose of the study was to determine the effect of progressive relaxation on anxiety in pregnant women with hypertension. The research employed a Quasi-Experimental approach using a pretest-posttest control group design with 60 participants. The participants were split into two groups: the intervention group (30 participants), who received progressive relaxation twice a day for 14 days, and the control group (30 participants), who received standard care. The Paired Sample T-Test revealed a noteworthy reduction in anxiety levels (p equal 0.000) among the intervention group. In contrast, the control group did not exhibit significant alterations in anxiety levels (p equal 0.746) after the treatment. Thus, progressive relaxation proves effective in reducing anxiety levels among pregnant women with hypertension. Future research should consider increasing the frequency and duration of interventions and exploring alternative approaches to further address hypertension issues during pregnancy.